1983
DOI: 10.1055/s-2008-1026051
|View full text |Cite
|
Sign up to set email alerts
|

Changes in Neuromuscular Performance in Voluntary and Reflex Contraction during Strength Training in Man

Abstract: Eleven male subjects went through heavy resistance strength training 3 times a week for 16 weeks. The training program consisted mainly of dynamic exercise for the knee extensor muscles with loads of 80%-120% of one maximum repetition in the squat lift. The investigation was undertaken to examine effects of strength training on neuromuscular performance both in voluntary and reflex contractions with special interest in their possible relationships. In addition to a large (P less than 0.001) increase in maximal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
31
1
1

Year Published

1988
1988
2016
2016

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 59 publications
(39 citation statements)
references
References 13 publications
2
31
1
1
Order By: Relevance
“…It is known that resistance exercise programs accompanied by muscle hypertrophy and task-specific performance may not necessarily increase maximal voluntary isometric strength (Brown et al 1990;Sale et al 1992;Higbie et al 1996), yet a large number of studies have reported such an effect (Hakkinen and Komi 1983;Young et al 1983;Jones and Rutherford 1987). The current finding of a somewhat greater increase in maximal voluntary isometric strength with enhanced eccentric compared with coupled concentric and eccentric resistance training is not at odds and consistent with other reports (Godard et al 1998;Hortobagyi et al 2001).…”
Section: Discussionsupporting
confidence: 87%
“…It is known that resistance exercise programs accompanied by muscle hypertrophy and task-specific performance may not necessarily increase maximal voluntary isometric strength (Brown et al 1990;Sale et al 1992;Higbie et al 1996), yet a large number of studies have reported such an effect (Hakkinen and Komi 1983;Young et al 1983;Jones and Rutherford 1987). The current finding of a somewhat greater increase in maximal voluntary isometric strength with enhanced eccentric compared with coupled concentric and eccentric resistance training is not at odds and consistent with other reports (Godard et al 1998;Hortobagyi et al 2001).…”
Section: Discussionsupporting
confidence: 87%
“…To determine the tibiofemoral contact forces for different gait tasks or populations some form of neuromusculoskeletal modelling may be necessary. This is because muscle activation patterns have been shown to be dependent on the control task [12], and to vary with both joint health [13] and training [38]. Thus, it seems unlikely that external measures, when used in statistical models that are inherently linear and non-dynamic, can predict joint contact forces during dynamic locomotor tasks.…”
Section: Discussionmentioning
confidence: 99%
“…Kubo et al (2001) reported a decrease in EMD after isometric training, but Zhou et al (1996) found no changes in EMD following sprint training. Similarly Hakkinen and Komi (1983) reported no significant differences in EMD values calculated under reflex contraction before and after 16 weeks of strength training. For healthy adults, data reported in the literature indicate that, for the TS muscle, the EMD value obtained from maximal electrical nerve stimulation are generally between 9.5 and 18.7 ms (Grosset et al 2005;Mora et al 2003;Muro and Nagata 1985;Winter and Brookes 1991).…”
Section: Introductionmentioning
confidence: 90%